Development of a conversion program to make SIMIND-generated SPECT data interfile acceptable to Xeleris. Issue 12 (December 2015) - Pandey, Anil K.; Kumar, Jay P.; Aheer, Deepak; Sharma, Anshul; Hasan, Binish; Patel, Chetan; Bal, Chandra S.; Kumar, Rakesh
Abstract : The Monte Carlo code SIMIND is used in nuclear medicine for research purposes, and also for testing the validity of various applications. Conversion of a SIMIND-generated interfile ( header and image data file) is required to process the simulated image data on a Xeleris workstation. Currently there is no conversion program provided with SIMIND to convert its interfile, which is acceptable in any nuclear medicine workstation. Manual editing of the header file is possible with any standard text editor but it is time-consuming (requiring ∼1 h) and stressful. To alleviate this, we have developed a conversion program using FreeMat V4.0 (an open source software similar to MATLAB from MathWorks). It takes an average of 0.04404 s to convert a SIMIND SPECT data interfile and make it acceptable to Xeleris.